The sharply nonlinear current – voltage characteristic of a structure with a quantum well built in the depletion region of a Schottky barrier - Korol, Anatoliy; Nosenko, I. (My University, 2012)
The heterostructure in which a quantum well is formed in the depletion region of the Schottky barrer is considered. The forward current – voltage characteristic of this structure is evaluated and analyzed.
Keywords: квантова яма; квантовая яма; quantum well; бар’єр Шоткі; тунельний струм; барьер Шоттки; туннельный ток; Schottky barrier; tunnel current; кафедра фізики та професійної безпеки